This is the show and the show is many things - This is the show and the show is many things 1994 Gent 17/09-27/11/1994; Museum van Hedendaagse Kunst Gent; Museum van Hedendaagse Kunst Gent (Gent : Snoeck-Ducaju, 1994)
Bourgeois, Louise ; Decock, Anne ; d'O, Honoré ; Hyber, Fabrice ; Kinoshita, Suchan ; Lehtonen, Henrietta ; Manders, Mark ; Rhoades, Jason ; Roosen, Maria ; Roudenko-Bertin, Claire ; Schaerf, Eran ; Tuymans, Luc ; Tzaig, Uri
This is the show and the show is many things, Museum van Hedendaagse Kunst, Gent, 1994-09-17. 1994-11-27
Engelse titel, Engelse en Nederlandse tekst
boek